Teks, Koteks, Dan Konteks Di Baliho: Analisis Wacana - Tri Indrayanti; Farida Y. Rosita; Aziz Fauzi (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
Language is an essential tool for communication. People use language to express feelings, desires, anxieties, joys, and so on. In the process of achieving goals, billboards play a crucial role in facilitating the delivery of information and messages. Even during political years, billboards are displayed along streets in major cities. The question arises, do the billboards we encounter around us have clear text, context, and context? Researchers are interested in addressing this issue. This study aims to describe the use of text, context, and context on billboards. The research method used is qualitative, utilizing reading and documentation methods. The research data sources are words and sentences accompanied by images on the billboards. The theory used is Dell Hymes' theory. The results of the analysis show that language is not only seen from the structure of the text, but also pay attention to the relationship between language, meaning, situation, and conditions of the text in social, cultural, political, and historical contexts. The three main aspects of text, context, and context are important in understanding how discourse is constructed and how hidden meanings can be revealed. Dell Hymes' theory, through the acronym SPEAKING, provides a guide for analyzing situational factors that influence discourse comprehension, such as setting, participants, purpose, sequence of actions, and linguistic norms. Data analysis shows that street billboards have clear elements of text, cotext, and context.